Natural products repurposing of the H5N1-based lead compounds for the most fit inhibitors against 3C-like protease of SARS-CoV-2 - Arli Aditya Parikesit; Rizky Nurdiansyah (GarVal Editorial Ltda., 2021)
Context: COVID-19 pandemic has caused more than 2.7 million mortality worldwide. Although the COVID-19 vaccine has been developed, the amount is still limited, and very few countries have reached 'herd immunity' level. In this regard, imported and community infections is still happening in the world. In order to complement the vaccine rollout, the drug is still necessary. Up to now, all the COVID-19 drugs in the market are still in emergency use, and their clinical application is still under tight surveillance. Thus, a breakthrough in drug development is necessary. Based on an extensive protein crystallography experiment, it is known that the 3C-like protease of SARS-CoV-2 plays an important role in the pathogenicity of the virus. Several inhibitors have been developed for this protein, including remdesivir that served as the standard in this experiment. However, recent findings in the wet lab also showed possible significant bioactivities for the repurposed influenza, and human rhinovirus leads for SARS-CoV-2. Previous research has developed flavonoid-based leads as H5N1 virus inhibitors. Aims: To develop lead compounds to inhibit 3C-like protease of SARS-CoV-2 from the existing H5N1 leads. Methods: The ligands and protein were prepared with energy minimization and the "add protonation" procedure. Then, the QSAR analysis was conducted to determine whether the ligands fit as leads for the 3C-like protease SARS-CoV-2 inhibitor. Molecular docking simulation was deployed for the selected ligand toward the 3C-like protease enzyme. Moreover, the molecular dynamics simulation was devised to examine the protein flexibility of the protease ligands. Results: It was found that only 9 out of the 19 repurposed H5N1-leads elicited significant QSAR-based properties for general antivirus, influenza antivirus, and antihuman rhinovirus bioactivities. In this regard, the leads were screened further with molecular docking, in silico ADME-TOX prediction, and molecular dynamics methods. Based on the further screen, the ligands of M00009235 and M00006834 were selected as lead compounds for 3C-like protease SARS-CoV-2 inhibitors. Conclusions: The ligands of M00009235 and M00006834 were selected as the best leads for inhibiting 3C-like protease of SARS-CoV-2 based on the virtual screening methods.